Interaction of Government and Taxpayer: Types of Taxpayers Created Through Tax Sanctions and Incentives - Filiz Baloğlu; Nazan Susam (International Journal of Public Finance, 2020)
The purpose of this study is to define the taxpayer types that are existing through determining the effects of tax sanctions and incentives (TSI) on taxpayer behaviors that are bonded with trust and power relations in the interaction of the society. TSIs existing in the tax system are tax policies that are used to regulate the tax world. These policies have the potential to change the relations and social interactions between government and taxpayer along with the increase in tax revenues. While the interacition derived from “clash” between government and taxpayers renders dominance and power as a prominent factor, a collaborative interaction provides more trust. In this context, establish tax compliance, together with taxpayers being homo economicus, the perspective of a social human setting forth the interaction and relations with its social environment should be taken into account as well. It could be seen that voluntarily compliant taxpayer type emerging in a modern tax system is a consequence of tax authority’s policy choices relying on relations with trust. Theoretically, the effects of new rules that TSIs’ have brought into the tax world on taxpayer behaviors presents the existence of taxpayer types that are; compulsorily compliant, compliant, and voluntarily compliant. It has been determined that strategic and compliant taxpayer types have emerged by relying on relationships with trust, while compulsorily compliant taxpayer types have emerged by relying heavily on relationships of power.